Decomposição da palhada de forrageiras em função da adubação nitrogenada após o consórcio com milho e produtividade da soja em sucessão - Garcia, Cássia Maria De Paula [UNESP] (2014)
The objective of this study was to evaluate the straw decomposition of the Urochloa and Panicum after intercropped with corn and nitrogen fertilization, as well as, the agronomic performance of soybean in succession. The experiment was conducted in an Oxisol in Cerrado conditions under no-tillage eight years ago. After the corn harvest intercropped with grass and cutting of forage homogenization were applied N rates (0, 50, 100 and 200 kg ha-1 of N - urea source) in coverage. The plots consisted of Urochloa brizantha,Urochloa ruziziensis and Panicum maximum Tanzânia and Mombaça sown at the time of corn sowing and subplots composed by accumulated amounts of nitrogen applied in forage plants prior to the soybean cultivation (0, 250, 500 and 1000 kg ha-1 of N, after five cuts). The experimental design was a randomized block with four replications in a split plot. Soon after the last cut of the forage, proportionate amount of fresh mass of the species of each subplot was wrapped in nylon bags called Litter Bags, these being deposited in direct contact with the soil, to determine the time of decomposition of the dry mass during a period of 150 days. The nitrogen doses, as well as, the corn intercropped with forages (except with Mombaça) interfere similarly in the straw decomposition of forage and in the soybean yield in succession. All the consortiums of corn and nitrogen fertilization predecessors determined that, at 60 days after desiccation and cutting, still remained between 50 and 60% of the initial straw for no-tillage system.